Solid state polymer ionogel electrolyte for use in Li‐ion batteries. (11th October 2020) - Zhan, Chi; Jana, Sadhan C.
Abstract: This work presents a preparation method for solid state ionogel electrolyte membranes intended for lithium‐ion batteries (LIBs). These membranes are obtained by filling the pores of syndiotactic polystyrene (sPS) gels with an ionic liquid (IL) that is later polymerized. The aim is to improve the thermal stability and mechanical properties in conjunction with mitigation of ionic liquid loss from ionogel electrolyte membranes at high application temperatures (>50°C). Such ionogel membranes circumvent the dimensional stability issues of polyolefin membranes at >90°C, volatility and flammability issues of organic liquid electrolytes, and ionic liquid loss due to thermal expansion of typical ionogel membranes. The ionogel membranes developed in this work contain a framework of high porosity sPS gel filled with an ionic liquid that is later polymerized via free‐radical polymerization. The resulting solid electrolyte membrane show improved thermal stability, good shape fixity, and negligible IL loss at high temperature. The electrolyte membrane also shows good electrochemical stability and adequate ionic conductivity due to high IL loading and high porosity of sPS gels. Abstract :